Obesidade infantil na perspectiva bioecológica do desenvolvimento humano - Moraes, Priscilla Machado (2015)
Childhood obesity is a growing public health problem, usually attributed to genetic predisposition. However, inadequate food intake, lifestyle, family environment personal and emotional characteristics of children and social issues also relate to excess of weight. In this study was analyzed the relationship between family and social systems and the personal attributes of obese children in the development of childhood obesity, enlighten by the Bioecological Theory of Human Development. The thesis is composed of three articles. The first, through a literature review, describes the method of Bioecological Theory of Human Development of Urie Bronfenbrenner, research from families with obese children. The second, identifies the influence of ecological contexts of obese children that can contribute to their state of obesity. Eight children participated, of both sexes, aged between eight and twelve years, and their responsible, five mothers and two grandmothers, aged between 34-64 years. All belong financially to the lowest social layer and are assisted by the Unified Health System (SUS). The instruments used were a form to collect biossocialdemographic data from clinical records, a semi-structured interview (with a specific guidelines for each group) and the Family Drawing (only with the children). Data were analyzed based on thematic content analysis technique and the projective test based on formal, general and content aspects. The results showed that children of this research are embedded in family systems marked by both suffered experiences and painful events as also overprotection. Grandparents interfere with the educational dynamics of parents. The relationship between brothers and colleagues is usually marked by rejection and conflict, which leads them to experience loneliness, causing losses to social relations of these children. The lack of consistency between what public policies profess related to the prevention of childhood obesity in the social sphere does not seem to favor the encouragement, support and protection to health care and the recommended action against the disease. The third, analyzes, through the cores of Person and Time in the Bioecological Modell, the personal characteristics and the history of life of obese children and their families that are interrelated in the genesis and maintenance of the disease. The methodological delineation was a multiple case study, which included two children, of both sexes and two mothers. The instruments used in the research were a form to collect biosocialdemographic data from the medical records, a semistructured interview and the Human Figure Drawing (done with the children). The results showed that children have difficulties related to their body image. Their stories reveal family secrets related to parental figures, transgenerational phenomena and mother / child characterized by low autonomy of the child leading to a lack of differentiation of the dyad hindering the domain of the problems.